La « Seconde Jamahiriyya » libyenne : l’échec d’une stratégie de survie - Jesús Jurado Anaya (L’Année du Maghreb)
The last ten years of the Gaddafi regime in Libya were characterized by the burden of tribalism and by the patrimonialisation of power around a number of elites related to the figure of Colonel Gaddafi. The differences between this form of sultanistic regime and the “classic” Jamahiriya established in 1977 led us to define the period between the end of the embargo and the February 2011 “revolution” as a “Second Jamahiriya.” This article attempts to explain the political developments in Libya since 1990 to better understand the fall of the Gaddafi regime and the current state of power fragmentation in the country.